PENINGKATAN KETERAMPILAN PROSES SAINS SISWA SMA NEGERI 1 PONOROGO MATERI GENTIKA MELALUI MODEL PROJECT BASED LEARNING - Sukardi, Sukardi; Nawawi, Nawawi (IKIP PGRI Pontianak, 2020)
The goal of this analysis is to assess the improvement in science process skills (SPS) and cognitive enhancement of Ponorogo 1 Public High School students on genetic material using the Project Based Learning model. This type of study is part of Classroom Action Research Studies. The study subjects included 36 students of class XII MIPA 1 at Ponorogo 1 Public High School. Data was obtained using the Science Process Skills (SPS) Task observation board, interview, final cycle reflection sheets, and test questions. . The data were analysed using qualitative and quantitative analysis. The results showed that there was an improvement in student cognitive learning outcomes and in the Science Process Skills (SPS) class XII MIPA 1 at Ponorogo 1 Public High School using the Project Based Learning model.